Seeing the wood and the trees: Sustainability education lessons from sustainable forest management - McDiarmid, Daniel; John, Michele; Wilson, Sam (Taylor and Francis, 2025)
Forests are critical ecosystems that are essential for human health and for mitigating the effects of climate change through the reduction of carbon in the atmosphere and their sequestration of carbon. However, increased global deforestation and exploitation of this vital resource have diminished these benefits. Sustainable forest management offers a number of values, principles and practices that can inform and enhance sustainability education. This chapter examines a number of important sustainability concepts that are applied in sustainable forest management, including carbon mitigation, an awareness of the challenges associated with the ‘Tragedy of the Commons’ and the important role of natural resource management, policy and regulation. These values and principles are applicable to a broad range of global natural resource issues and can provide valuable knowledge and understanding in the development and presentation of sustainability education.